2006
DOI: 10.1074/jbc.m608055200
|View full text |Cite
|
Sign up to set email alerts
|

The Human Renin Kidney Enhancer Is Required to Maintain Base-line Renin Expression but Is Dispensable for Tissue-specific, Cell-specific, and Regulated Expression

Abstract: Renin is the rate-limiting enzyme in the renin-angiotensin system and thus dictates the level of the pressor hormone angiotensin-II. The classical site of renin expression and secretion is the renal juxtaglomerular cell, where its expression is tightly regulated by physiological cues. An evolutionarily conserved transcriptional enhancer located 11 kb upstream of the human RENIN gene has been reported to markedly enhance transcription in renin expressing cells in vitro. However, its importance in vivo remains u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
47
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 51 publications
(44 reference statements)
4
47
0
Order By: Relevance
“…These data fit with recent evidence challenging the role of the renin enhancer in the regulation of renin expression in vivo. 22 On the other hand, the mouse renin enhancer was shown to be critical for the salt-dependent control of renin synthesis in transgenic mice. 23 Thus, the role of the renin enhancer in the regulation of renin gene expression in vivo remains to be further clarified.…”
Section: Discussionmentioning
confidence: 99%
“…These data fit with recent evidence challenging the role of the renin enhancer in the regulation of renin expression in vivo. 22 On the other hand, the mouse renin enhancer was shown to be critical for the salt-dependent control of renin synthesis in transgenic mice. 23 Thus, the role of the renin enhancer in the regulation of renin gene expression in vivo remains to be further clarified.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] It has been reported recently that deletion of the mouse 6 or human 7 enhancer in genetically engineered mice leads to a marked reduction in renin in renal juxtaglomerular (JG) cells, which are the classical source of circulating renin. Telemetry studies of mouse renin enhancer knockout (REKO) mice revealed normal diurnal rhythm of blood pressure, but at a mean 9 mm Hg lower level.…”
mentioning
confidence: 99%
“…Renin levels in mice are much higher than in humans suggesting that the enhancer may be more active in mice. Although the enhancer is conserved among mammalian renin genes, there are some critical differences that markedly influence the level of enhancer activity (Zhou et al, 2006). Several decades ago, the observation that renal renin secretion responds to osmotic change either in renal perfusate or in the microenvironment of juxtaglomerular cells, prompted many investigations.…”
Section: Reninmentioning
confidence: 99%